Mcdonald, Machaela. A Ghostly Adventure. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Machaela Mcdonald, a Grade 8 student at Beaconsfield Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Machaela writes, "The story came from me and my friend Sabrina when we used to take 'adventures' in the giant woods behind her backyard. She was telling me this one time when she was 7 or 8 when her brother and few street friends went up and they found a cabin, but every time after she could never find it, until this one time when we managed to find the cabin, and something else."